(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Entrepreneurship management training programs have gained significant attention as a meansto drive rural development and empower women in various societies around the world. These programsfocus on equipping individuals, particularly those in rural areas, with the necessary knowledge, skills, andresources to become successful entrepreneurs. By addressing the specific needs and challenges facedby rural communities and women, entrepreneurship management training plays a crucial role infostering socio-economic progress and gender equality. Rural areas often encounter unique barriers todevelopment, including limited access to resources, inadequate infrastructure, and a lack of economicopportunities. These challenges contribute to persistent poverty and inequality within thesecommunities. Similarly, women in rural areas face additional obstacles, such as cultural norms, limitededucation opportunities, and restricted access to financial resources and decision-making power.Consequently, their potential contributions to economic growth and community development remainlargely untapped. This paper aim to study the impact of entrepreneurship management training on ruraldevelopment women empowerment.